"Please Miss, Please!": An observational study of young people's social and emotional experiences post-transition to secondary school. (July 2022) - Mahmud, Arif
The secondary school transition is considered a critical life event by practitioners and researchers alike, and the challenges presented by the pupils during this transition continues to be high-profile in educational, social and political contexts. This study focused on Year 7 pupils aged 11 to 12 years old in their first year of secondary school. Classroom observations of around 120 pupils using an open framework recording procedure offered real-time insights into the everyday lived experiences of these adolescents. The paper illustrates the skills and behaviours that children brought to their secondary school transition, and as such reveals how the transition should be perceived as both an event and a social and emotional learning process. The findings of this study highlight the challenges of flexibility and diversity within peer networks after the move to secondary school and the impact the transition can have on the pupils' sense of self. The analysis is discussed in terms of implications for schools, practitioners and researchers with suggestions for further studies with this under-researched and vulnerable group.